Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let ( L, ≤ ) be a lattice, x, y, z ∈ L

I am unable to understand why ( x ∧ z ) ∧ ( y ∧ z ) = z ∧ ( y ∧ x ) is mentioned as fact in Y.N. Singh's "Mathematical Foundation of Computer Science" - Pg 157

Could I prove this somehow, or is it an axiom?

share|improve this question
    
Both sides equal the infimum of the set $\{x,y,z\}$. –  Robin Chapman Nov 22 '10 at 21:21

1 Answer 1

There are at least two ways to do this:

  • As Robin Chapman suggests, show that each side of the equation is just the infimum of the set $\{x,y,z\}$

  • Prove that $\wedge$ is an associative and commutative operation, and then use this to reduce the left side to $x \wedge y \wedge (z \wedge z)$ which is $x \wedge y \wedge z$ because $z \wedge z = z$.

share|improve this answer
    
Well, I get it that $( x ∧ z ) ∧ ( y ∧ z ) = ( ∧ { x, z } ) ∧ ( ∧ { y, z } ) = ∧ { x, y, z }$ From this, I am comfortable saying that : $∧ { x, y, z } = ( x ∧ y ) ∧ ( x ∧ z ) ∧ ( y ∧ z )$ But from here I cannot proceed to show that this is equivalnet to $z ∧ ( y ∧ x )$ Even it were given, say, $y ≤ z, ( z ∧ y ) = y$ We could say, $∧ { x, y, z } = ( x ∧ y ) ∧ ( x ∧ z ) ∧ y$ But from here I cannot proceed to show that this is equivalnet to $z ∧ ( y ∧ x )$ –  user3740 Nov 23 '10 at 0:14
    
I was able to show that both sides equal the infimum of the set $\{x,y,z\}$, but I do want to know how I can proceed from the information in my above comment. –  user3740 Nov 23 '10 at 1:03

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.